Conditional Capital Practice in Empagae Village, Wattang Sidenreng District, Sidenreng Rappang Regency (Islamic Economic Law Perspective) - Faradhillah, Nitha; Rusdi, M. Ali; Muliati (SIGHAT: JURNAL HUKUM EKONOMI SYARIAH, 2022)
The practice of conditional capital that occurs in Empagae Village is an economic activity that involves two parties, namely: the lender and the borrower. This conditional capital loan started from a borrower who needed capital to purchase seeds and farm fertilizers, who then borrowed a sum of money by offering conditions for the loan that had been given, namely "if the borrower lends one million, he will give one pikul of rice as long as the loan has not been paid. returned". The purpose of this study is to analyze the conditional capital system that occurs in Empagae Village from the perspective of Islamic Economic Law. The research method used in this study uses descriptive qualitative research methods. In collecting data, the methods of field observation, interviews, and documentation were used. The results of this study indicate that 1) The form of conditional capital practice in Empagae Village has two parties, Wa'Tati as the borrower makes a loan by providing conditions in the form of giving one pikul of rice for each loan with a value of one million he does. The existence of additions in debts according to Islamic economic law is not allowed if there is an addition that exceeds the principal loan or the addition is a condition of the loan. 2) Judging from the number of additions in this conditional lending practice, it can contain an additional element or usury, due to the benefits that are almost equivalent to the amount of the loan that has been borrowed, of course this is not in accordance with Islamic law.